A European survey of management approaches in chronic urticaria in children: EAACI pediatric urticaria taskforce. Issue 1 (12th October 2021) - Tsabouri, Sophia; Arasi, Stefania; Beken, Burcin; Church, Martin K.; Alvaro‐Lozano, Montserrat; Caffarelli, Carlo; Flohr, Carsten; Janmohamed, Sherief R.; Konstantinou, George N.; Lau, Susanne; Lefevre, Sebastien; Mortz, Charlotte G.; et al.
Abstract: Background: Although well described in adults, there are scarce and heterogeneous data on the diagnosis and management of chronic urticaria (CU) in children (0–18 years) throughout Europe. Our aim was to explore country differences and identify the extent to which the EAACI/GA²LEN/EDF/WAO guideline recommendations for pediatric urticaria are implemented. Methods: The EAACI Task Force for pediatric CU disseminated an online clinical survey among EAACI pediatric section members. Members were asked to answer 35 multiple choice questions on current practices in their respective centers. Results: The survey was sent to 2, 773 physicians of whom 358 (13.8%) responded, mainly pediatric allergists (80%) and pediatricians (49.7%), working in 69 countries. For diagnosis, Southern European countries used significantly more routine tests (eg, autoimmune testing, allergological tests, and parasitic investigation) than Northern European countries. Most respondents (60.3%) used a 2 nd ‐generation antihistamine as first‐line treatment of whom 64.8% updosed as a second line. Omalizumab was used as a second‐line treatment by 1.7% and third line by 20.7% of respondents. Most clinicians (65%) follow EAACI/WAO/GA2LEN/EDF guidelines when diagnosing CU, and only 7.3% follow no specific guidelines. Some clinicians prefer to follow national guidelines (18.4%, mainly Northern European) or the AAAAI practice parameter (1.7%). Conclusions: Even though most members of the Pediatric Section of EAACI are familiar with the EAACI/WAO/GA2LEN/EDF guidelines, a significant number do not follow them. Also, the large variation in diagnosis and treatment strengthens the need to re‐evaluate, update, and standardize guidelines on the diagnosis and management of CU in children.